Cosmology, astrobiology and the RNA world: just add quintessential water. Issue 2 (7th April 2021) - Johnson, Keith
Abstract: Laboratory generation of water nanoclusters from amorphous ice and strong terahertz (THz) radiation from water nanoclusters ejected from water vapour into a vacuum suggest the possibility of water nanoclusters ejected into interstellar space from abundant amorphous ice-coated cosmic dust produced by supernovae explosions. Water nanoclusters (section 'Water nanoclusters') offer a hypothetical scenario connecting major mysteries of our Universe: dark matter (section 'Baryonic dark matter'), dark energy (section 'Dark energy'), cosmology (section 'Cosmology'), astrobiology (section 'Astrobiology') and the RNA world (section 'The RNA world') as the origin of life on Earth and habitable exoplanets. Despite their expected low density in space compared to hydrogen, their quantum-entangled diffuse Rydberg electronic states make cosmic water nanoclusters a candidate for baryonic dark matter that can also absorb, via the microscopic dynamical Casimir effect, the virtual photons of zero-point-energy vacuum fluctuations above the nanocluster cut-off vibrational frequencies, leaving only vacuum fluctuations below these frequencies to be gravitationally active, thus leading to a possible common origin of dark matter and dark energy. This picture includes novel explanations of the small cosmological constant, the coincidence of energy and matter densities, possible contributions of the red-shifted THz radiation from cosmic water nanoclusters at redshift z ≅ 10 to the cosmic microwave background (CMB) spectrum, the Hubble constant crisis, the role of water as a known coolant for rapid early star formation and ultimately, how life may have originated from RNA protocells on Earth and exoplanets and moons in the habitable zones of developed solar systems. Together, they lead to a cyclic universe cosmology – based on the proposed equivalence of cosmic water nanoclusters to a quintessence scalar field – instead of a multiverse based on cosmic inflation theory. Recent CMB birefringence measurements may support quintessence. Finally, from the quantum chemistry of water nanoclusters interacting with prebiotic organic molecules, amino acids and RNA protocells on early Earth and habitable exoplanets, this scenario is consistent with the anthropic principle that our Universe must have those properties which allow life, as we know it – based on water, to develop at the present stage of its history.